2006
DOI: 10.1128/jcm.00265-06
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine Resistance of Hepatitis B Virus Masked by Coemergence of Mutations in Probe Region of the COBAS AMPLICOR Assay

Abstract: The COBAS AMPLICOR hepatitis B virus assay targets a conserved region of the genome and is widely used to monitor treatment of hepatitis B in order to identify emerging resistance. However, the assay failed to recognize increasing viremia levels when YMDD mutations were paralleled by mutations in the segment targeted by the COBAS AMPLICOR probe.The aim of treating chronic hepatitis B virus (HBV) infection is to prevent the emergence of liver cirrhosis or hepatocellular carcinoma. Currently, treatment is given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…This study reported that the COBAS AMPLICOR monitor assay failed to recognize increasing levels of viraemia in individuals on treatment due to core mutations that develop during treatment. [9] This assay, which uses the manual nucleic acid extraction protocol and the real-time Taqman chemistry, is very sensitive and can potentially be used to detect occult HBV infection. The total assay duration is 5.5-6 hours, including the extraction protocol.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported that the COBAS AMPLICOR monitor assay failed to recognize increasing levels of viraemia in individuals on treatment due to core mutations that develop during treatment. [9] This assay, which uses the manual nucleic acid extraction protocol and the real-time Taqman chemistry, is very sensitive and can potentially be used to detect occult HBV infection. The total assay duration is 5.5-6 hours, including the extraction protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of HBV DNA in the liver tumor and the more sensitive HBV serum DNA assay suggested a case of OBI. Indeed, the failure of commercial HBV assays to detect HBV DNA has been reported, particularly in patients harboring treatment-resistant mutations [20] . This highlights the need for a more rigorous HBV DNA assay test and reinforces the need to target at least three different locations in the HBV genome [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the former, the Abbott RealTime assay offers the advantage of a much wider dynamic range (38 to 38,000 IU/ml for the Amplicor assay) and improved probe selectivity. The probe of the Cobas Amplicor HBV Monitor test targets a sequence in the viral DNA core region, and the sensitivity of the assay may be compromised with respect to viral strains bearing mutations in this region (17) and genotype F variant strains (12,31). In contrast, the Abbott RealTime assay probe hybridizes within a highly conserved region of the S gene, allowing accurate detection of all viral strains evaluated.…”
Section: Discussionmentioning
confidence: 99%